R.M. Ballantyne (1825-1894) - Cockburn, R.H. (ARCTIC, 1984)
More than a few northern men of the late nineteenth and early twentieth centuries - particularly those raised in Scotland and England - have attested in their memoirs to the seductive tug they felt as boys when reading Ballantyne's books about the Canadian North. It is something of a happy irony, given his own uneasy and brief period of service with the Hudson's Bay Company, that Ballantyne's boys' novels 'The Young Fur Traders' (1855) and 'Ungava' (1857) and, more especially, his personal account of that service, 'Hudson's Bay; or Every-Day Life in the Wilds of North America' (1848), recruited so many able young men for both the HBC and Revillon Freres. As Ballantyne's six years in Rupert's Land and the King's Posts, and his narrative of that experience, are the cynosure of this profile, the balance of his life must be dealt with summarily. . It is for Hudson's Bay that we still remember Ballantyne. Detailed and valuably informative, the account is enlivened by youthful intensity. As well as describing fur trade operations, it contains powerful evocations of terrain, waterways, and weather, and shrewd sketches of an assortment of personalities. .